2020
DOI: 10.1055/s-0040-1712166
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Postpartum Hemorrhage Admission Risk Factor Stratification in a Large Obstetrics Population

Abstract: Objective This study aimed to evaluate the performance of the California Maternal Quality Care Collaborative (CMQCC) admission risk criteria for stratifying postpartum hemorrhage risk in a large obstetrics population. Study Design Using detailed electronic health record data, we classified 261,964 delivery hospitalizations from Kaiser Permanente Northern California hospitals between 2010 and 2017 into high-, medium-, and low-risk groups based on CMQCC criteria. We used logistic regression to assess a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 38 publications
7
42
0
1
Order By: Relevance
“…14 Similar to previous work, we found that patients who were scored as medium or high risk for hemorrhage had significantly higher odds of receiving a transfusion compared with lowrisk patients. 14,16,23 Using the CDC criteria for SMM, transfusion has been documented as the most prevalent indicator for SMM. 4,18 As expected, transfusion was a driving factor for the association of hemorrhage risk score with SMM in our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Similar to previous work, we found that patients who were scored as medium or high risk for hemorrhage had significantly higher odds of receiving a transfusion compared with lowrisk patients. 14,16,23 Using the CDC criteria for SMM, transfusion has been documented as the most prevalent indicator for SMM. 4,18 As expected, transfusion was a driving factor for the association of hemorrhage risk score with SMM in our study.…”
Section: Resultsmentioning
confidence: 99%
“…We were unable to obtain specific data regarding the "history of postpartum hemorrhage," which is required to assign a medium-risk CMQCC score, because it cannot reliably be extracted from larger administrative databases with ICD-10 diagnosis codes. 16 Obstetrical hemorrhage was identified by ICD-10 diagnosis codes and was assigned at the discretion of individual providers at our institution. Our institution generally utilizes the American College of Obstetricians and Gynecologists' (ACOG) definition to diagnose clinically significant obstetrical hemorrhage.…”
Section: Methodsmentioning
confidence: 99%
“…Assessments of the CMQCC have shown a statistically significant difference in risk for PPH between women in low-, medium-and high-risk groups. However, this same tool has consistently classified more than 40% of PPH cases as low-risk because they had no risk factors upon admission [18,21,22]. The tool underestimates risk for various definitions of severe PPH, as well as PPH defined as >1000mL cumulative blood loss.…”
Section: Background and Significancementioning
confidence: 99%
“…Current risk stratification efforts for PPH have relied primarily on known risk factors (e.g., prior Cesarean delivery) [20]. While these factors are significant predictors of PPH, in many cases, PPH occurs in women with no known risk factors [11,18,21]. Considering this, we included both known risk factors and thousands of potential predictors extracted from EMR to maximize our ability to detect any patterns of clinical information that increase risk for PPH.…”
Section: Feature Engineering and Selectionmentioning
confidence: 99%
“…An important strategy to reduce PPH related adverse outcomes is routine assessment of PPH risk upon admission for delivery 16 . Limited tools have been previously developed to predict PPH risk.…”
Section: Introductionmentioning
confidence: 99%